Adaptive Behavior of Dynamic Orthoester Cryptands. (13th December 2016) - Shyshov, Oleksandr; Brachvogel, René‐Chris; Bachmann, Tobias; Srikantharajah, Rubitha; Segets, Doris; Hampel, Frank; Puchta, Ralph; von Delius, Max
Abstract: The integration of dynamic covalent bonds into macrocycles has been a tremendously successful strategy for investigating noncovalent interactions and identifying effective host–guest pairs. While numerous studies have focused on the dynamic responses of macrocycles and larger cages to various guests, the corresponding constitutionally dynamic chemistry of cryptands remains unexplored. Reported here is that cryptands based on orthoester bridgeheads offer an elegant entry to experiments in which a metal ion selects its preferred host from a dynamic mixture of competing subcomponents. In such dynamic mixtures, the alkali metal ions Li +, Na +, K +, Rb +, and Cs + exhibit pronounced preferences for the formation of cryptands of certain sizes and donor numbers, and the selection is rationalized by DFT calculations. Reported is also the first self‐assembly of a chiral orthoester cryptate and a preliminary study on the use of stereoisomers as subcomponents. Abstract : Jeder Topf findet seinen Deckel : Cryptanden mit Orthoesterfunktionen als Brückenköpfen ermöglichen elegante Experimente, in denen ein Metallion seinen bevorzugten Wirt aus einer dynamischen Mischung konkurrierender Unterkomponenten selektiert. Die Alkalimetallionen Li +, Na +, K +, Rb + und Cs + begünstigen die Bildung von Cryptanden bestimmter Größe und Donoranzahl.